Pemanfaatan Teknologi Digital Sebagai Strategi Efektif Meningkatkan Literasi Sains di Sekolah Dasar - Atmojo, Setyo Eko; Wardana, Ari Kusuma (Jayapangus Press, 2025)
The low scientific literacy of elementary school students, influenced by conventional teaching methods and lack of interactivity, necessitates innovation through digital technology. This study aims to test the effectiveness of digital technology as a strategy to enhance scientific literacy using a quasi-experimental method with a pretest-posttest control group design. The subjects consisted of 60 fifth-grade students from two elementary schools (30 students in the experimental group and 30 in the control group). The experimental group received science instruction integrating digital tools such as virtual laboratories (Labster) and educational applications (Quizizz) over 8 weeks, while the control group used conventional methods. Research instruments included a scientific literacy test (HOTS-based questions) and student activity observation sheets. Data were analyzed quantitatively using t-test and ANOVA to compare improvements in scientific literacy scores between the groups. Results showed that the experimental group achieved a significant increase in scientific literacy scores (N-Gain 0.72) compared to the control group (N-Gain 0.32). The study concludes that systematic integration of digital technology effectively enhances elementary students' scientific literacy.